Respuesta :

Answer:

2nd answer.

Step-by-step explanation:

see attached.

Ver imagen marcthemathtutor

Answer with Step-by-step explanation:

We have to find the solution of the equation:

[tex]x^4+6x^2+5=0[/tex]

Let u=x²

Then, above equation is transformed to:

[tex]u^2+6u+5=0[/tex]

it could also be written as:

[tex]u^2+5u+u+5=0[/tex]

u(u+5)+1(u+5)=0

(u+1)(u+5)=0

either  u+1=0 or u+5=0

either u= -1 or u= -5

Putting u=x²

x² = -1 or x² = -5

On taking square root both sides

x= ± i  or  x= ± i√5

Hence, roots of the equation [tex]x^4+6x^2+5=0[/tex] are:

i , -i , i√5 and -i√5

ACCESS MORE